Exploring state level factors associated with short-stays in child welfare: the role of systemic risk and surveillance - Greenfield, Brett (Child maltreatment, 2023)
Growing attention has been directed toward children who are placed in out-of-home care by child welfare authorities for less than 30 days, deemed ?short-stayers?. This exploratory study uses multiple national child welfare and population data sources to identify macro level factors associated with short-stays. Two-level logistic regression modeling was conducted to explore how state-level factors were associated with risk of short-stays. Factors associated with lower odds of short-stays included living in a state with a centralized child welfare reporting structure and with greater food insecurity. Factors associated with greater odds included living in a state with a higher percentage of the state?s population enrolled in the Supplemental Nutrition Assistance Program and states with more police per capita. Multiple state level factors were associated short-stay risk, which suggests broader systemic factors contribute to these brief removals. Findings suggest greater surveillance by police and social services increases risk of short-stays, which likely have implications for child welfare policy and practice.